Generalized Convolutional Sparse Coding with Unknown Noise - Wang, Yaqing (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2020)
Convolutional sparse coding (CSC) can learn representative shift-invariant patterns from multiple kinds of data. However, existing CSC methods can only model noises from Gaussian distribution, which is restrictive and unrealistic. In this paper, we propose a generalized CSC model capable of dealing with complicated unknown noise. The noise is now modeled by Gaussian mixture model, which can approximate any continuous probability density function. We use the expectation-maximization algorithm to solve the problem and design an efficient method for the weighted CSC problem in maximization step. The crux is to speed up the convolution in the frequency domain while keeping the other computations involving weight matrix in the spatial domain. Besides, we simultaneously update the dictionary and codes by nonconvex accelerated proximal gradient algorithm without bringing in extra alternating loops. The resultant method, called generalized convolutional sparse coding (GCSC), obtains the same space complexity and a smaller running time compared with existing CSC methods. Extensive experiments on synthetic and real-world noisy data sets validate that GCSC can model noise effectively and obtain high-quality filters and representations